Refractory agitation in the NICU: challenges in prevention, diagnosis, and treatment - Kim Beatty; Eunsung Cho; Jessica Biggs; Shawnee Daniel-McCalla; Johana Diaz (Frontiers in Pediatrics)
In this paper we explore refractory agitation in the neonatal population, focusing on the limitations of existing evidence on appropriate prevention, diagnosis, and treatment options. We highlight seven patients identified in an urban single-center level IV NICU with agitation unresponsive to standard non-pharmacologic interventions and escalation of standard neurosedative medications. We analyzed baseline characteristics and clinical courses of these patients with the aim to identify the NICU subpopulation at greatest risk for development of refractory agitation and to gain insight into the potential benefits of alternative medical management of agitation on later neurodevelopment. Based on these experiences we propose a practical approach to infants at increased risk for refractory agitation including standardized screening guidelines and a clinical pathway for developmentally appropriate non-pharmacologic and pharmacologic management.